Analytical Study of Natakusthadi Yoga with special reference to Their Vishaghna Effects (International Journal of Ayurveda and Pharma Research, 2022)
Nata & Kushta medicinal plants are easily available in Indian diaspora and both are widely used in many Agada as Vishaghna dravya mentioned in classical texts. Both have reported acetylcholinesterase and Phospholipase A2 enzyme inhibiting property in many Research studies. The quality of Nata, Kustha & Nata Kustha Yoga was evaluated based on organoleptic, physico-chemical, and microbial quality parameters. Loss on drying at 105°C, Total ash, Acid Insoluble ash, Alcohol-soluble extractive, Water-Soluble extractive, HPTLC and pH value parameters were evaluated as per WHO guidelines, Ayurvedic pharmacopoeia and Indian pharmacopoeia. Analytic analysis of Nata, Kustha & Nata Kusthadi Yoga in this study found to be under standard limit. Standardization test done on Natakusthadi Yoga helped in authenticating the preparation and in ensuring quality of the same. The Natakusthadi Yoga prepared by following standard operative procedures should have Loss on drying at 105°C, Total ash, Acid Insoluble ash, Alcohol-soluble extractive, Water-Soluble extractive and pH value is 2.1%, 4.8%, 0.32%, 42.9%, 37.8% & 5.5 respectively